GENDER AND MUSLIM WOMEN - Jihan Abdul Rahman Oshiesh (English Department, STKIP PGRI Bandar Lampung, 2020)
God created the human male and female; to achieve the integration of the two pillars of the reconstruction of this universe. The concept of gender is that the differences between male and female are based primarily on social rather than biological criteria, meaning that societies determine the expected roles of Adam and Eve .To date, the concept of gender can be viewed favorably, as it may help to understand the forms of discrimination against women and help the struggle to give them their legitimate rights to employ, develop and enrich their capacities more effectively to serve themselves, their families and society, away from stereotypes and narrow roles. This issue was discussed at the international meeting in the seventies of the last century to the eighties to crystallize a public issue has become widespread and dealt with the development of the possibilities of communication. But we rarely receive writings on this subject in the eyes of the Islamic religion and how to address this issue